PATTERN OF POTASSIUM RELEASE FROM SLOW RELEASE FERTILIZER POTASSIUM SULFATE-BENTONITE FERTILIZER - P, Suarya; W, Sudiarta I; H, Krisjayanto (Jurnal Ilmu Pendidikan Indonesia, 2023)
Potassium is a macro nutrient element that is needed by plants. Potassium plays a role in plant metabolism, maintains turgor, and forms stronger stems. Sadly. Potassium is easily lost through washing because it is easily soluble in water. This is what triggers plants to often experience a lack of potassium. Efficiency in the use of potassium fertilizers can be increased through the formulation of fertilizers made in the form of slow release (Slow Release Fertilizer), namely by controlling the solubility of the substance in water through fertilizer coating. The purpose of this study was to determine the potassium content obtained, the largest mass of SRF fertilizer, and the pattern of potassium release in the soil after being bound by acid-activated bentonite in the manufacture of potassium sulfate SRF. Coating of potassium sulfate with bentonite was carried out with a mass of 10 bentonite; 20; 30; 40; and 50 grams with a mass of 10 grams of potassium sulfate. Total potassium levels were analyzed by atomic absorption spectrophotometer. The results of the analysis of potassium levels obtained the levels of each SRF fertilizer with the code SRF 10: SRF 20: SRF 30: SRF 0; and SRF so respectively 4.41: 5.49: 6.06: 6.54; and 7.01 mg/g with the maximum concentration obtained from SRF sa fertilizer. Furthermore, the potassium release test was carried out using the percolation method with distilled water for potassium sulfate-bentonite SRF fertilizer with a ratio of 10:50. release test using time variation every 1 week period for 1 month. As a result, the average potassium level was obtained, namely 11.51; 38.33; 51.37; and 72.24% w/b. Based on the results of this release test it is known that potassium. experience a slow release pattern in the soil.